Broadening the Circle: Creativity, Regeneration and Redistribution in Value Loops - Palakshappa N; Venkateswar S; Ganesh S (Emerald)
Increasing industrial agriculture and economic crisis has generated creative responses in pursuit of responsible solutions to the human and environmental cost of globalization by applying these models to promote social responsibility, help sustain livelihoods and foster biodiversity. A key issue concerns how responsible and circular businesses might provide appropriate responses to large-scale ‘wicked’ problems. This paper asks what such creativity looks like in the context of a circular economy that attempts to build closed value loops, by examining a case from the organic cotton textile industry: Appachi Eco-Logic. We use an ethnographic extended-case approach to identify two phases of creative growth at Appachi Eco-Logic, examining how closing the value loop and creating circularity involved broadening the circle to include more and more actors. We identify two major challenges to achieving and maintaining full circularity before concluding with a broad provocation for the study of circular economies.
Keywords: circular economy; creativity; regeneration; redistribution; value loops; 1503 Business and Management; 1605 Policy and Administration; 1608 Sociology